Restoring wetlands on intensive agricultural lands modifies nitrogen cycling microbial communities and reduces N2O production potential. (1st December 2021) - Kasak, Kuno; Espenberg, Mikk; Anthony, Tyler L.; Tringe, Susannah G.; Valach, Alex C.; Hemes, Kyle S.; Silver, Whendee L.; Mander, Ülo; Kill, Keit; McNicol, Gavin; Szutu, Daphne; Verfaillie, Joseph; et al.
Abstract: The concentration of nitrous oxide (N2 O), an ozone-depleting greenhouse gas, is rapidly increasing in the atmosphere. Most atmospheric N2 O originates in terrestrial ecosystems, of which the majority can be attributed to microbial cycling of nitrogen in agricultural soils. Here, we demonstrate how the abundance of nitrogen cycling genes vary across intensively managed agricultural fields and adjacent restored wetlands in the Sacramento-San Joaquin Delta in California, USA. We found that the abundances of nirS and nirK genes were highest at the intensively managed organic-rich cornfield and significantly outnumber any other gene abundances, suggesting very high N2 O production potential. The quantity of nitrogen transforming genes, particularly those responsible for denitrification, nitrification and DNRA, were highest in the agricultural sites, whereas nitrogen fixation and ANAMMOX was strongly associated with the wetland sites. Although the abundance of nosZ genes was also high at the agricultural sites, the ratio of nosZ genes to nir genes was significantly higher in wetland sites indicating that these sites could act as a sink of N2 O. These findings suggest that wetland restoration could be a promising natural climate solution not only for carbon sequestration but also for reduced N2 O emissions. Highlights: Land use type is the main determinant for N2 O production potential in the Delta. All processes (nitrification, denitrification, DNRA) contribute to N2 O production. Drained soils show the highest N2 O production potential. Wetland restoration will increase the potential for N2 O reduction to N2 . Restored wetlands in the Delta have high nitrogen fixing potential.